Вплив медитації на параметри біоелектрографії (кірліанографії) та варіабільності серцевого ритму і артеріального тиску - Бабелюк, В.Є.; Дубкова, Г.І.; Попович, І.Л. (Медична гідрологія та реабілітація, 2010)
Впервые показано, что медитация в виде молитвы у иконы благоприятно влияет на состояние регуляторных систем (оцененное по вариабильности ритма сердца) у лиц с их перенапряжением, что сопровождается закономерными изменениями параметров биоэлектрографии (кирлианографии). For the first time is shown, that the meditation as a pray at an icon favorably influences a condition of regulatory systems (appreciated on heart rhythm variability) at the persons from them overstrain, that is accompanied by natural changes of parameters of bioelectrography (kirlianography).